2021
DOI: 10.1177/24755303211020677
|View full text |Cite
|
Sign up to set email alerts
|

Authorial Conflicts of Interest and Sponsorship in Systematic Reviews and Meta-Analyses on Psoriasis

Abstract: Background: Because industry influence – in the form of study sponsorship and authorial conflicts of interest (COI) – can bias the results and conclusions of systematic reviews, there is a need to understand their role in systematic reviews, particularly for common conditions like psoriasis. Objectives: This study identifies conflicts of interest and industry-author relationships in systematic reviews on psoriasis treatment. Methods: Consistent with our cross-sectional design, we searched MEDLINE and Embase fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Further, industry funded clinical trials have been shown to contribute to physician scepticism regarding the efficacy of medications 28. Among industry funded SRs, Kee et al 29 highlight an AbbVie-sponsored SR demonstrating the clinical superiority of risankizumab to adalimumab—the market leader for the treatment of psoriasis 30. This finding is important, because both drugs are manufactured by AbbVie, and adalimumab’s patent is set to expire in 2023 31.…”
Section: Discussionmentioning
confidence: 99%
“…Further, industry funded clinical trials have been shown to contribute to physician scepticism regarding the efficacy of medications 28. Among industry funded SRs, Kee et al 29 highlight an AbbVie-sponsored SR demonstrating the clinical superiority of risankizumab to adalimumab—the market leader for the treatment of psoriasis 30. This finding is important, because both drugs are manufactured by AbbVie, and adalimumab’s patent is set to expire in 2023 31.…”
Section: Discussionmentioning
confidence: 99%